2016
DOI: 10.1002/chem.201504813
|View full text |Cite
|
Sign up to set email alerts
|

On the Mesoporogen‐Free Synthesis of Single‐Crystalline Hierarchically Structured ZSM‐5 Zeolites in a Quasi‐Solid‐State System

Abstract: Hierarchically structured zeolites (HSZs) have gained much academic and industrial interest owing to their multiscale pore structures and consequent excellent performances in varied chemical processes. Although a number of synthetic strategies have been developed in recent years, the scalable production of HSZs single crystals with penetrating and three-dimensionally (3-D) interconnected mesopore systems but without using a mesoscale template is still a great challenge. Herein, based on a steam-assisted crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 53 publications
(36 reference statements)
0
29
0
Order By: Relevance
“…Figure a shows the XRD patterns of the synthesized HSZ series materials and microporous ZSM‐5 zeolites in the 2 θ range of 5–50°. All of them demonstrate the typical and similar diffraction patterns of MFI‐type zeolite irrespective of post‐synthesis dealumination or CLD of TEOS treatment, indicating their high crystallinity and high stability . Figure b shows their N 2 sorption isotherms and the textural properties are summarized in Table .…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Figure a shows the XRD patterns of the synthesized HSZ series materials and microporous ZSM‐5 zeolites in the 2 θ range of 5–50°. All of them demonstrate the typical and similar diffraction patterns of MFI‐type zeolite irrespective of post‐synthesis dealumination or CLD of TEOS treatment, indicating their high crystallinity and high stability . Figure b shows their N 2 sorption isotherms and the textural properties are summarized in Table .…”
Section: Resultsmentioning
confidence: 65%
“…Accordingly, Figure a gives the NH 3 ‐TPD profiles of HSZ series and microporous ZSM‐5 and the calculated acid amounts are listed in Table . All of the HSZ series feature two desorption bands similar to that of microporous ZSM‐5, in which the high‐temperature and low‐temperature band correspond to the strong and the weak acid sites, respectively ,. Because the strong acidity of ZSM‐5 zeolites originates from the isomorphous substitution of framework Si by Al, the change of Al content and/or Al coordination state would induce the variation of acid amount and/or acid strength.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…[171] Ge et al succeeded in the synthesis of single-crystalline mesoporous ZSM-5 having an abundant 3D interconnected network based on the SAC method using small amounts of TPAOH. [172] The method was also applicable for high-silica crystals. [173] Similarly, Rilyanti et al also used a TPA + lean SAC, and found that the presence of mesopores is attributed to the presence of severe defect sites.…”
Section: Zsm-5mentioning
confidence: 99%
“…2C), which demonstrates that the introduction of mesopores maintains the single crystal integrity. 36,37 Most importantly, these ultrane nanocrystals tend to agglomerate into the larger secondary particles with a loose structure, which may be attributed to their high surface Gibbs free energy. 38 The abundant intercrystalline mesopores in the HA-ZSM-5 zeolite were formed by aggregation of ultrane nanocrystals with sizes of 10-20 nm.…”
Section: Morphology Observation and Controlmentioning
confidence: 99%